ANALISIS SWOT STRATEGI PEMBERDAYAAN MASYARAKAT PROGRAM PENATAAN LINGKUNGAN PERMUKIMAN KOMUNITAS DI KELURAHAN SURYATMAJAN, KOTA YOGYAKARTA - Nurasih Shamadiyah (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2017)
Community empowerment has wide meaning from various point of view. Community empowerment is the emphasis on the behavior of self-sustaining local communities as a system that breaks down themselves. Communities have the right to determine strategies for empowerment strategies according to their strengths, weaknesses, opportunities, and threats. Analysis of empowerment strategies through SWOT analysis for strategies that can be in accordance with the characteristics of society. This research was conducted at the priority location of Community Based Settlement Environment (PLPBK) program of Kelurahan Suryatmajan with number of informant 30 people and sampling technique using snowball sampling to find an information. From the analysis result, based on aformentioned reasons there are 4 segments of community empowerment point in the priority areas, namely handicraft and food industry, eco-green area, green open space area, and river arrangement. The determination of community empowerment strategy is the initial stage of overall empowerment activities, because the initial stage can determine the category of society and the pattern of empowerment to be undertaken